Antiplasmodial activity of Cryptolepis sanguinolenta alkaloids from leaves and roots - Paulo, A (2015)
The roots of Cryptolepis sanguinolenta have been investigated for their chemical composition since 1931 but so far no studies on the leaves have been reported although they are used in traditional medicine in Guinea-Bissau. Two new alkaloids identified as cryptolepinoic acid (1) and methyl cryptolepinoate (2) and the known alkaloids cryptolepine (4), hydroxycryptolepine (5/5a) and quindoline (6), were isolated from the ethanolic and chloroformic leaf extracts. Aqueous and ethanolic extracts of the leaves and roots and seven alkaloids isolated from those extracts were tested in vitro against Plasmodium falciparum K1 (multidrug-resistant strain) and T996 (chloroquine-sensitive clone). All the extracts were shown to give 90% inhibition of P. falciparum K1 growth at concentrations 23 mu g/ml. Cryptolepine (4) was the most active alkaloid tested with IC50 values (0.23 mu M to K1; 0.059 mu M to T996) comparable with chloroquine (0.26 mu M to K1; 0.019 mu M to T996). The indolobenzazepine alkaloid cryptoheptine (7) was the second most active with IC50 values of 0.8 mu M (K1) and 1.2 mu M (T996). Cryptolepinoic acid (1) showed no significant activity while its ethyl ester derivative 3 was active against P. falciparum K1 (IC50